Dynamical quantum phase transitions in an atom-molecule system - Yixiao Huang; Jialu Yin; Yuguo Su; Enjia Ye; Zhengda Hu; Yi Ding (AIP Advances)
We conduct an investigation on the dynamical quantum phase transition within an atom-molecule Bose–Einstein condensate. We explore the dynamics of atom-molecule conversion and utilize the fraction population of the atom as an order parameter for probing dynamical quantum phase transitions. It is shown that the quench dynamics of the atom presents a non-analytical change regarding the atom binding energy, and it is demonstrated that this dynamics can detect both the quantum phase transition at the ground state and at the highest energy level. Furthermore, we analyze the dynamics of the Loschmidt echo and present its connection with the dynamical quantum phase transitions.